A potential overestimation of CO 2 physiological effects on evapotranspiration - Yi Hao; Xing Yuan; Xiazhen Xi; Zhenzhong Zeng; Giovanni Forzieri; Peili Wu (Proceedings of the National Academy of Sciences, 2026)
It is generally believed that CO 2 physiological forcing can partially mitigate land surface drying under global warming by reducing stomatal conductance and evapotranspiration. Most of this type of study focuses on the direct regulation by vegetation physiology, overlooking interactive feedback from the atmosphere. Using fully coupled earth system model simulations, we find that the physiological benefit may have been optimistically overestimated. Vegetation-induced energy change may in turn further affect atmospheric vapor pressure deficit (VPD), exerting extra evapotranspiration demand indirectly. Indirect VPD feedback over northern mid-high latitudes could offset 54% (±26%) of evapotranspiration reduction driven by stomatal closure under current CO 2 condition, and that proportion increases to 68% (±18%) at 4 × CO 2 . The enhanced VPD feedback is largely driven by vegetation-mediated albedo decline and temperature rise in northern mid-high latitudes, which intensifies evapotranspiration loss as stomatal constraints are minimal. These are important findings, substantially limiting the physiological benefits of CO 2 with extra pressure on surface aridification and water resources.